Elasticities of Demand for U.S. Exports: A Comment - Deppler, Michael C. (The Review of Economics and Statistics, 1971)
[1] Ezekiel, H., and J. Adekunle, Secular Behavior of Income Velocity: An Intermational Cross Section Study, IMF Staff Papers, vol. XVI, no. 2, July 1969, 224-239. [2] Goldsmith, R. W., The Determinants of Financial Structure, Organization for Economic Cooperation and Development, Paris, 1966, 27-30. [3] Khazzoom, J. D., The Currency Ratio in Developing Countries (New York: Frederick A. Praeger, 1966). [4] Melitz, J. and H. Correa, International Differences in Income Velocity, this REviEW LII (Feb. 1970), 12-17. [5] Wallich, H. C., Theory and Quantity Policy, Ten Economic Studies in the Tradition of Irving Fisher (New York: John Wiley & Sons, Inc., 1967), 257-280.